UPAYA UNI EROPA (UE) DALAM MENANGANI KRISIS PENGUNGSI DI KAWASAN UNI EROPA - Lalu Puttrawandi Karjaya (Bajang Institute, 2022)
The refugee crisis that has occurred in the EU region since 2015 has left the EU overwhelmed and has to seek ways to overcome the crisis as the crisis inevitably pose a threat to both the EU and the refugees. This paper describes the various attempts by the EU to address these issues with the challenges it faces. Using the concept of